Effect of Resistance Training on Extracellular Matrix Adaptations in Skeletal Muscle of Older Rats - Guzzoni, Vinicius; Ribeiro, Manoel B. T.; Lopes, Gisele N.; de Cássia Marqueti, Rita; de Andrade, Rosângela V.; Selistre-de-Araujo, Heloisa S.; Durigan, João L. Q. (Frontiers in Physiology, 2018)
Accumulation of connective tissue, particularly extracellular matrix (ECM) proteins, has been observed in skeletal muscles with advancing age. Resistance training (RT) has been widely recommended to attenuate age-induced sarcopenia, even though its effects on the components that control ECM turnover in skeletal muscles remain to be elucidated. Thus, the aim of this study was to determine the effects of RT on connective tissue content and gene expression of key components of ECM in the skeletal muscles of aged rats. Young (3 mo.) and old (21 mo.) adult male Wistar rats were submitted to a RT protocol (ladder climbing with 65, 85, 95 and 100% load), 3 times a week for 12 weeks. Forty-eight hours post-training, the soleus (SOL) and gastrocnemius (GAS) muscles were dissected for histological and mRNA analysis. RT mitigated the age-associated increase of connective tissue content in both muscles, even though mRNA levels of COL-1 and -3 were elevated in old trained rats. Overall, RT significantly elevated the gene expression of key components of connective tissue deposition (TGFβ and CTGF; MMP-2 and-9; TIMP-1 and -2) in the GAS and SOL muscles of old rats. In conclusion, RT blunted the age-induced accumulation of connective tissue concomitant to the upregulation of genes related to synthesis and degradation of the ECM network in the SOL and GAS muscles of old rats. Although our findings indicate that RT plays a crucial role reducing connective tissue accumulation in aged hindlimb muscles, key components of ECM turnover were paradoxically elevated. The phenotypic responses induced by RT were not accompanied by the gene expression of those components related to ECM turnover.